Strategy Analysis of Batik MSME Development - Anggraeni, Siska; Srijani, Ninik; Wibawa, Ramadhan Prasetya (Universitas Negeri Semarang, 2021)
This study aimed to analyze the strategies used by MSMEs of Batik Murni in developing their business. The informants in this study were 18 people. The method used was a qualitative approach. Data collection techniques used observation, interviews, documentation, and triangulation. Data analysis techniques used data reduction, data presentation and data verification. The results showed that: (1) The use of cost leadership strategies, differentiation strategies and focus strategies had an important effect on the development of MSMEs of Batik Murni. (2) The factors that affected the development strategy of MSMEs of Batik Murni consisted of capital, labor and marketing. (3) The raw materials used by MSMEs of Murni Batik in the production process were cloth and silk cloth, canting, for textile dyes by using remasol, naptol and indigosol and natural dyes, for washing by using waterglass. (4) The capital of MSMEs of Batik Murni was obtained from personal capital, capital loans to the East Java Regional Bank and to PT Industri Kereta Api (INKA). (5) The sales system used by MSMEs of Batik Murni was a direct and indirect sales system. (6) MSMEs of Batik Murni used a marketing research strategy, sales research, marketing information systems, marketing plans and evaluation. (7) The impact of the development strategy for MSMEs of Batik Murni Madiun, namely an increase in the amount of production, an increase in the amount of marketing and finally an increase in income.